2006
DOI: 10.1111/j.1460-9568.2006.05087.x
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal changes in respiratory activity in rat in vitro and modulatory effects of substance P

Abstract: Developmental changes in the respiratory activity and its modulation by substance P (SP) were studied in the neonatal rat brainstem-spinal cord preparation from the day of birth to day 3 (P0-P3). The respiratory network activity in the ventrolateral medulla was represented by two types of bursts: basic regular bursts with typical decrementing shape and biphasic bursts appearing after augmented biphasic discharges in inspiratory neurons. With advancing postnatal age the respiratory output was considerably modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 83 publications
(200 reference statements)
1
7
0
Order By: Relevance
“…This finding is supported by a previous report which shows that the basic frequency of respiratory rhythm increases and becomes faster from P0 to P3 in rat brainstem-spinal cord preparations (Shvarev and Lagercrantz, 2006). Since there are significant changes in frequency between injured and non-injured animals within specific time groups, this suggests that the hemisection injury induced the change of respiratory frequency.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is supported by a previous report which shows that the basic frequency of respiratory rhythm increases and becomes faster from P0 to P3 in rat brainstem-spinal cord preparations (Shvarev and Lagercrantz, 2006). Since there are significant changes in frequency between injured and non-injured animals within specific time groups, this suggests that the hemisection injury induced the change of respiratory frequency.…”
Section: Discussionsupporting
confidence: 90%
“…However, the developmental pattern of respiratory frequency in the hemisected animals is the same as the non-hemisection controls. In general, the developmental change of the respiratory frequency suggests that the respiratory rhythm generation and the transformation by the motoneurons of rhythmic inspiratory drive into appropriate patterns of respiratory output continue to mature postnatally (Greer and Funk, 2005; Shvarev and Lagercrantz, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, our model predicts that loss of the positive feedback from preBötC to Raphe will result in decreased frequency or even loss of rhythmicity for some degrees of neuromodulatory tone. It has been shown that in the neonatal rat brainstem-spinal cord preparation, the effects of SP can be biphasic at the very early age (P0–P1), with an initial drop or even cessation of the rhythm and prolonged period of increased frequency (Shvarev and Lagercrantz, 2006). This finding is identical to results of our model for the weak feedback strengths.…”
Section: Discussionmentioning
confidence: 99%
“…For more mature preparations (P2–P3) SP did not induce a decrease in respiratory frequency, which is similar to our modeling results for larger values of positive feedback. Therefore, one possible interpretation of Shvarev and Lagercrantz (2006) experiments for early post-natal experiment is an increase in positive feedback between the Raphe and preBötC during the first few days of postnatal life. It has been reported that victims of sudden infant death syndrome (SIDS) have multiple defects in the serotonergic system (Duncan et al, 2010; Paterson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Under increasing hypoxia, SP manifests as natural anti-hypoxant and is not only involved in nociception mechanisms but also in brain adaptation to oxygen deficiency (40). SP-ergic system was found to be more active in regulating the respiratory responses during the early postnatal period in neonatal rat brainstem–spinal cord preparation (41) and medullary slice preparations of newborn mice (42). But surprisingly, SP was not found to control ventilatory rhythm generation in fetal rats, and it was hypothesized that, may be, SP does not modulate the generation of respiratory responses before birth and affects the phrenic motoneurons only after birth (43).…”
Section: Neurokinin Receptorsmentioning
confidence: 99%